Differences of phenylalanine concentrations in dried blood spots and in plasma: erythrocytes as a neglected component for this observation - Haas, Dorothea; Hauke, Jana; Schwarz, Kathrin V.; Consalvi, Lucia; Trefz, Friedrich K.; Blau, Nenad; Hoffmann, Georg F.; Burgard, Peter; Garbade, Sven; Okun, Jürgen G. (Metabolites, 2021)
Monitoring phenylalanine (Phe) concentrations is critical for the management of phenylketonuria (PKU). This can be done in dried blood spots (DBS) or in EDTA plasma derived from capillary or venous blood. Different techniques are used to measure Phe, the most common being flow-injection analysis tandem mass spectrometry (FIA-MS-MS) and ion exchange chromatography (IEC). Significant differences have been reported between Phe concentrations in various sample types measured by different techniques, the cause of which is not yet understood. We measured Phe concentrations in 240 venous blood samples from 199 patients with hyperphenylalaninemia in dried blood spots, EDTA plasma and erythrocytes by FIA-MS-MS and IEC. Phe concentrations were significantly lower in erythrocytes than in plasma leading to about 19% lower Phe DBS concentrations compared with plasma independent from the method used for quantification. As most therapy recommendations for PKU patients are based on plasma concentrations reliable conversion of DBS into plasma concentrations is necessary. Variances of Phe concentrations in plasma and DBS are not linear but increases with higher concentrations indicating heteroscedasticity. We therefore suggest the slope of the 75th percentile from quantile regression as a correction factor.
Gesehen am 01.12.2021